Effect of Work Motivation, Work Environment, and Organizational Culture on Employee Performance - Parmansyah, Abdul (YUME : Journal of Management, 2025)
Employee performance is a crucial factor in organizational success. This study examines the impact of work motivation, work environment, and organizational culture on employee performance. Using a quantitative research method, data was collected from employees across various industries through structured questionnaires. The findings indicate that work motivation, work environment, and organizational culture have a significant positive effect on employee performance. The study highlights that fostering a supportive work environment and cultivating a strong organizational culture can enhance employee motivation and overall performance. Implications for human resource management practices are also discussed. Keywords: Work Motivation, Work Environment, Organizational Culture, Employee Performance